Disasters and Religious Resilience in Indonesia: A Review - Nikmah, Dzihni Durratun; Abdullah Muslich Rizal Maulana (Jurnal Studi Agama, 2024)
Various disasters that occur in Indonesia are caused by several factors that can trigger casualties, environmental damage, property losses, and even adverse psychological impacts. The presence of such disasters causes pressure on disaster victims both from external and internal factors that can raise doubts or difficult situations that can threaten one's religious practice. This paper aims to show the role of religious communities towards disaster victims in Indonesia in order to increase the religious resilience of people affected by disasters. From the results of the research that has been done, it can be concluded that disaster victims in Indonesia will be able to go through the difficulties and pressures caused by disasters if they stick to religious practices and teachings socialized by religious communities. Religion teaches many important things concerning social benefit. Individuals and communities who feel pressure and sadness when faced with trials must hold fast to religious values in order to survive and find a way out of the complexity of the problem at hand.